Physico-Chemical, Microbiological and Sensory Quality of Chicken and Beef Stored in Home Refrigerator - Md Adnan, Md Adnan; Yadav, Sunil; Kumar Yadav, Saroj; Alam, Mahabub (Journal of Meat Science, 2026)
The purpose of this study was to ascertain how long raw chicken meat and beef meat kept at 4°C in a typical home refrigerator would last. Researchers from Chattogram Veterinary and Animal Sciences University performed an extensive examination over five days, assessing 10 meat samples (five chicken meat and five beef meat) obtained from local markets in Chattogram (Jhawtola, Bahaddar Hat, and Chawk Bazar). The quality assessment encompassed physico-chemical, microbiological, and sensory criteria, including pH, water holding capacity (WHC), extract release volume (ERV), protein degradation (tyrosine value), fat oxidation (TBARS), total viable microbial count (TVC), and aroma. Significant data indicated a gradual deterioration in quality for both types of meat. Sensory evaluation indicated a significant escalation in offodours, becoming especially evident by the fifth day. Physicochemical research revealed a steady decrease in pH for chicken, whereas beef pH exhibited greater variability. The water-holding capacity was minimal for both meats on the penultimate day. Moreover, elevated tyrosine and TBARS levels indicated continuous breakdown of proteins and lipids, respectively. Microbiologically, beef had a greater overall viable count compared to chicken. The study revealed that whereas beef demonstrated a more rapid decomposition rate, both meats underwent considerable quality degradation by the fifth day of refrigerated storage. These findings point out the importance of appropriate raw meat handling and timely storage techniques for preserving domestic food safety and quality.